PELAKSANAAN TINDAKAN KEPOLISIAN PENGGUNAAN KEKUATAN OLEH BRIGADE MOBILE POLISI DAERAH KALIMANTAN BARAT BERDASARKAN PERATURAN KEPALA KEPOLISIAN NEGARA REPUBLIK INDONESIA NOMOR 1 TAHUN 2009 - NIM. A1012201150, MUHAMMAD LUQMAN ADHAIRIL (Fakultas Hukum Universitas Tanjungpura, 2024)
Abstrac The title of the research thesis: Implementation of Police Actions on the Use of Force by the West Kalimantan Police Mobile Brigade Based on the National Police Chief's Regulation Number 1 of 2009, with the problem formulation: How is the implementation or execution of the Police Action on the Use of Force by the West Kalimantan Regional Police Mobile Brigade Based on the National Police Chief's Regulation Number 1 of 2009? What are the factors that influence the role of the West Kalimantan Police Mobile Brigade unit in enforcing National Police Chief Regulation Number 1 of 2009? The results of academic research show that the application of Police discretion through the application of the principle of legality of rights chosen by members of the National Police Mobile Brigade has not been carried out in a standard manner at the implementation level, due to the normative nature of the National Police Regulations, namely, on the one hand, the police regulations stipulated by the National Police Chief are based on statutory regulations.-a higher invitation or in accordance with externally binding authority (Article 1 number 4 Regulation of the Head of the National Police of the Republic of Indonesia Number 2 of 2018, Article 15 paragraph 1 letter e in conjunction with Article 18 paragraph (1), (2) Law Number 2 2002 or categorized as organic legislation implementing Article 30 paragraph 5 of the 1945 Constitution of the Republic of Indonesia, namely those that implement orders from higher statutory regulations or in accordance with the authority possessed by the Police Institution of the Republic of Indonesia. Meanwhile, on the other hand, this type of regulation National Police Chief, Police Regulations stipulated by the National Police Chief and applicable to all police work areas which have internally binding legal force, (article 1 point 5 of the Regulation of the Head of the National Police of the Republic of Indonesia Number 2 of 2018), which is part of the police regulations of the Republic of Indonesia which have internal binding legal force, so that at the practical level there needs to be legal certainty, in addition to fulfilling legal benefits and legal justice for members Brimob Polri in the form of regulations or Standard Operating Procedures (SOP) regulations, in this case in the form of West Kalimantan Province Police Chief Regulations, so that at the practical level the legal facts do not cause legal problems in the implementation of police actions, because they must comply in accordance with statutory regulations, while the procedural facts are only focuses on the stages and pays attention to the conditions in the field faced by and at the choice of members of the National Police Mobile Brigade in West Kalimantan, therefore, the application of police discretion by members of the police and/or Police Mobile Brigade officers, especially those who have authority in accordance with the provisions of Law Number 2 of 2002, namely Article 18 Paragraph (1), should require further elaboration in the form of standard operational procedures according to police law, so that discretionary actions are carried out by police officers or especially the Police Mobile Brigade unit as the spearhead of law enforcement and community order, and a unitary state. Republic of Indonesia, regulations only provide guidelines for members of the National Police in carrying out police actions and without standard SOPs that are possible in the stages of conditions in the field that occur in the case of excessive use of force or cannot be legally accounted for based on Police Regulations. The factors currently influencing this are the first factor influencing the West Kalimantan Regional Police Mobile Brigade in using force in police actions, namely the geographical area of West Kalimantan and the precise distribution of the West Kalimantan Regional Police Mobile Brigade units which have not followed the procedures as regulated in the provisions of Article 46 paragraph (3) National Police Chief Regulation Number 14 of 2018 concerning Organizational Structure and Work Procedures at Regional Police Level, West Kalimantan Police Mobile Brigade Unit. The second factor is the amount of adequate or routine training as mandated in CHAPTER III Article 11 paragraph (1) and (2) of the National Police Chief Regulation Number 1 of 2009, in fact the amount of training that exists does not meet the procedural standards that lead to the use of force in police actions in regarding understanding and application of police discretion, because there is more physical training and temporary handling based on a priority scale with a number that is not comparable to the current number of Brimob Polda Kal-Bar personnel. The third factor is inadequate supervision and control and there are still vacancies in the organizational structure of the West Kalimantan Police Mobile Brigade, elements of the West Kalimantan Police Mobile Brigade leadership structure, as mandated by Article 14 paragraph (1) of the Republic of Indonesia National Police Chief Regulation Number 1 of 2009.Keywords: Use of Force, Police Legal Action, Discretion Abstrak Judul skripsi penelitian: Pelaksanaan Tindakan Kepolisian Penggunaan Kekuatan oleh Brimob Polda Kalimantan Barat Berdasarkan Peraturan Kapolri Nomor 1 Tahun 2009, dengan perumusan masalah: Bagaimana implementasi atau pelaksanaan Tindakan Kepolisian Penggunaan Kekuatan oleh Brimob Polda Kalimantan Barat Berdasarkan Peraturan Kapolri Nomor 1 Tahun 2009? Bagaimana faktor-faktor yang mempengaruhi Peran satuan Brimob Polda Kalimantan Barat dalam menegakan Peraturan Kapolri Nomor 1 Tahun 2009 ? Hasil penelitian secara akademis,bahwa penerapan diskresi Kepolisian melalui penerapan prinsip legalitas hak yang dipilih oleh anggota Brimob Polri, belum terlaksana secara standar pada tataran implementasi, dikarenakan secara normatif Peraturan Polri, yaitu Pada satu sisi peraturan kepolisian yang ditetapkan oleh Kapolri adalah berdasarkan perintah peraturan perundang-undangan yang lebih tinggi atau sesuai kewenangan yang mengikat secara eksternal (Pasal 1 angka 4 Peraturan Kepala Kepolisian Negara Republik Indonesia Nomor 2 Tahun 2018, Pasal 15 ayat 1 huruf e jo Pasal 18 ayat (1),(2) Undang-Undang Nomor 2 Tahun 2002 atau dikategorikan sebagai peraturan perundang-undangan organik pelaksanaan Pasal 30 ayat 5 UUD Negara Republik Indonesia Tahun 1945, yaitu yang melaksanakan perintah peraturan perundang- undangan yang lebih tinggi atau sesuai kewenangan yang dimiliki oleh Lembaga kepolisian Republik Indonesia. Sedangkan pada sisi lain jenis Peraturan Kapolri, Peraturan Kepolisian yang ditetapkan oleh Kapolri dan berlaku untuk seluruh wilayah kerja kepolisian yang mempunyai kekuatan hukum yang mengikat secara internal. (pasal 1 angka 5 Peraturan Kepala Kepolisian Negara Republik Indonesia Nomor 2 Tahun 2018), yang merupakan bagian dari peraturan kepolisian Republik Indonesia yang kekuatan hukum mengikat bersifat internal, sehingga dalam tataran praktek perlu ada kepastian hukum, disamping memenuhi kemanfaatan hukum serta keadilan hukum bagi Anggota Brimob Polri dalam bentuk regulasi atau peraturan Standar Operasi Prosedur (SOP) dalam hal ini dalam bentuk Peraturan Kapolda Provinsi Kalimatan Barat, sehingga pada tataran prakek fakta hukumnya tidak menimbulkan problematika hukum penerapan tindakan kepolisian, karena wajib patuh sesuai dengan peraturan perundangan, sedangkan fakta prosedurnya hanya terfokus pada tahapan serta memperhatikan kondisi situasi kondisi dilapangan yang dihadapi oleh dan atas pilihan anggota Brimob Polri di Kal- Bar, oleh karena itu, penerapan diskresi kepolisian oleh anggota kepolisian dan atau pejabat Brimob Polri, khususnya yang memiliki wewenang sesuai dengan ketentuan Undang-Undang Nomor 2 Tahun 2002 yakni Pasal 18 Ayat (1), seharusnya wajib penjabaran lebih lanjut dalam bentuk standar operasional prosedur secara hukum kepolisian, agar tindakan diskresi yang dilakukan oleh petugas kepolisian atau khususnya kesatuan brimob Polri sebagai ujung tombak penegakan hukum dan keananan masyarakat, dan negara kesatuan Republik Indonesia, regulasi hanyalah memberi pedoman bagi anggota Polri dalam pelaksanaan tindakan kepolisian dan tanpa SOP yang standar yang dimungkinkan dalam tahapan kondisi di lapangan yang terjadi dalam hal penggunaan kekuatan yang berlebihan atau tidak dapat dipertanggungjawabkan secara hukum berdasarkan Peraturan Kepolisian. Adapun faktor yang mempengaruhi saat ini, yaitu faktor Pertama yang mempengaruhi Brimob Polda Kalbar dalam melakukan penggunaan kekuatan dalam Tindakan kepolisian, yaitu faktor luas geografi Kalbar dan penyebaran penempatan satuan Brimob Polri Polda Kal- Bar yang belum mengikuti prosedur sebagaimana diatur dalam ketentuan Pasal 46 ayat (3) Peraturan Kapolri Nomor 14 Tahun 2018 tentang Susunan Organisasi dan Tata Kerja Pada Tingkat Kepolisian Daerah, Satuan Brimob Polda Kalbar. Faktor kedua adalah Jumlah pelatihan yang memadai atau rutin sebagaimana yang diamanahkan pada BAB III Pasal 11 ayat (1) dan (2) Peraturan Kapolri Nomor 1 Tahun 2009, faktanya jumlah Pelatihan yang ada jumlah belum memenuhi standar prosedur yang mengarah penggunaan kekuatan dalam tindakan kepolisian dalam hal pemahaman, dan penerapan diskresi kepolisian, karena lebih banyak pelatihan fisik dan penanganan yang bersifat temporer berdasarkan skala prioritas dengan jumlah yang tak sebanding dengan jumlah personil Brimob Polda Kal-Bar saat ini. Faktor ketiga adalah belum memadai pengawasan dan pengendalian dan masih kekosongan dalam jabatan struktur organisasi Brimob Polda Kal-Bar unsur struktur Pimpinan Brimob Kal-Bar, sebagaimana diamanahkan Pasal 14 ayat (1) Peraturan Kepala Kepolisian Negara RI Nomor 1 Tahun 2009.Kata Kunci: Penggunaan Kekuatan, Tindakan Hukum Kepolisian, Diskresi